A ciência da informação e a inteligência de estado: um estudo de caso do programa nacional de proteção do conhecimento sensível da agência brasileira de inteligência - Isabella Moreira dos Santos (2016)
This work aims to analyse and to contribute with the National Program for Sensitive Knowledge Protection (NPSKP) of the Brazilian Intelligence Agency by the Science of Information expertise support. In this matter, we consider crossing points between the Science of Information and the Intelligence State, which present relevant interdependences. The methodological approach had the deductive method as an academic manner of reference, which contributed to develop a theoretical construct, to identify revealed interfaces and to create categories which goal is to scrutinize this research theme: the NPSKP. Furthermore, related to the categories it can be mentioned the Strategic Information Contexts, the Strategic Integration of Information and Knowledge Management, the International Economic Environment Monitoring and the Integrity of National Patrimony which were applied in the structural, systemic and informational NPSKP milieu. In this way, we consider this thesis main achieved results the intelligence system improvement, the knowledge and intellect development to uphold assertive decision-making strategies, the knowledge sharing encouragement and the enhancement of economic intelligence.